Rural High School English Teacher Online Teaching: Practices and Strategies - Joko Prayudha S (Journal of English Development, 2022)
The Covid-19 virus has spread throughout the world both in cities and in remote areas. The spread of the corona virus has caused the cessation of various kinds of human activities, including in the educational aspect. Teachers in rural places have faced many challenges in teaching during the pandemic. This is due to the many obstacles and problems faced by teachers during the pandemic. This study aims to describe the practices and strategies that teachers apply when teaching English in rural school. The method used in this research is qualitative using a descriptive approach. Data was collected through questionnaires via Google form and interviews via Whatsapp. The results of the study show that teachers who teach in rural places face many obstacles when teaching, such as; the lack of internet access and mastery of technology owned by students are also low motivated in leaning. In addition, teachers do more home teaching as one of their responsibilities to assist students in providing a better understanding of the english material. Keywords: rural place, online teaching, practices, strategies